Optimalisasi Peran Guru dalam Era Kontemporer: Perspektif Menejemen Dakwah Berdasarkan al-Qur’an Surah Ali Imran [3]: 79 - Yuniarti, Fani Firda (Fakultas Dakwah UIN KHAS Jember, 2024)
Amid the noble duties of a teacher, the position of teachers in the education system of this country continues to struggle with various issues, including teacher welfare, the functional status of teachers as temporary staff, and the contractual teaching system that seemingly equates teachers with outsourced labor. Additionally, the government has proposed a policy to sell teachers' services through marketplace platforms. Are teachers' services comparable to commercial goods? Where is the respect for teachers and their duties? This study employs a library research approach. The findings on optimizing the role of teachers from the perspective of the Qur'an, Surah Ali Imran [3]: 79, reveal that the policy of placing teachers on a marketplace does not position teachers as the central figures of education aimed at producing a